Toward a Theory of Liking. Issue 2 (13th May 2013) - Burke, Kevin; Greteman, Adam
Abstract: In the current essay, Kevin Burke and Adam Greteman challenge this thing called love by looking at how we might instead "like" in education. Within education, multiculturalism can be viewed as a way of loving, or learning to love, diversity and, as such, learning to love the self; this tendency is notably apparent in the recent rise of concern expressed about student self‐esteem. According to the authors, however, critical research on multiculturalism demonstrates how, in loving diversity, multicultural discourses limn the possibilities for subjects to come into being and be liked for their differences. Drawing on James Alison's On Being Liked, Burke and Greteman reframe the problem of relating in education instead through the language of liking. How does the shift from loving to liking — either our students, our teachers, or ourselves — create different social dynamics and ethical paradigms? In engaging this question, Burke and Greteman offer an alternative model of liking that is based on the practice of cruising.